Benefits of the Social and Environmental Responsibility Program (TJSL) PT. Jasa Raharja Tk.I Medan to the Success of MSMEs in Medan City - Nurul Annisa; Muhammad Yafiz (Penerbit Jurnal Indonesia, 2022)
In BUMN, corporate social responsibility has been regulated in the Minister of BUMN Regulation No. PER-09/MBU/07/2015 regarding PKBL. PT Jasa Raharja as a BUMN must follow the policies set by the Minister of BUMN, one of which is the creation of a PKBL Unit according to the Regulation of the Minister of BUMN No. PER-09/MBU/07/2015. This study aims to find out what the benefits of the CSR program are to the success of MSMEs. This research was conducted at PT Jasa Raharja (Persero) Representative Tk.1 Medan. The method used in this research is qualitative method . The data collection technique used is literature study and field study. Based on the results of research and discussion, it can be concluded that the Social and Environmental Responsibility Program is very beneficial for the success of MSMEs in the city of Medan. This is caused by many factors, such as the process that is passed and the requirements needed are very easy and not difficult, the amount of loans given is also considered to be sufficient to meet the needs of MSME owners. The community (especially MSMEs) really need financial assistance to expand their business so that their business is able to compete with other larger businesses, therefore the partnership program is felt to be very helpful for the community. This CSR program is also useful for improving good relations between the company and the surrounding community.